Experimental and numerical investigation of transverse shear behavior of glass-fibre composites with embedded vascular channel. (15th November 2020) - Demiral, Murat; Tanabi, Hamed; Sabuncuoglu, Baris
Abstract: Interply and interplay damage behavior of glass fiber composites with microvascular channels were investigated in this study. Short beam flexural tests and finite element analysis were performed according to ASTM D2344 for two stacking configurations, [90/0]3s and [0/90]3s . Specimens with and without channel (control specimens) were analyzed to investigate the channel effect in detail. In the finite element simulations, the intraply matrix damage was modeled using a continuum damage mechanics based LarC04 damage initiation criterion, implemented via a user-defined VUMAT subroutine in ABAQUS/Explicit. Interlaminar damage was modeled using cohesive zone elements that were introduced between the plies. Experimentally and numerically obtained load-displacement curves and failure patterns were in good agreement. The influence of the presence of vascular channel on the flexural response of the composite short beams was in-depth analyzed. An increase in the shear strength of channeled specimens was observed for [90/0]3s compared to the control samples.